Project Tools@Schools:immersive – Tasks for a critical use of genera-tive AI in immersive foreign language sequences in subject teaching - Ferris-Diederich, Catherine; Wild, Sandrine; Negrinelli, Stefano (Babylonia (Asssociation Babylonia Suisse), 2025)
With rapid advancements in digital translation and AI, there is a growing need for materials promoting a reflective use of AI for language learning. Therefore, in the Tools@Schools:immersive project, we develop tasks to enhance digital and foreign language skills while supporting generative AI in immersive foreign language sequences (îlots immersifs). So far, we have developed two tasks – adaptable to various languages for the subjects home economics and history, and utilize AI tools such as ChatGPT to foster cooperative AI interaction. This approach enhances both language learning and content understanding, while also promoting critical thinking and autonomous learning.